2009
DOI: 10.1037/a0014578
|View full text |Cite
|
Sign up to set email alerts
|

Promoting academic achievement: The role of racial identity in buffering perceptions of teacher discrimination on academic achievement among African American and Caribbean Black adolescents.

Abstract: In this study, the authors examined the moderating effects of different dimensions racial identity (i.e., racial centrality and public regard) on perceptions of teacher discrimination and academic achievement among a nationally represented sample of African American and Caribbean Black adolescents. The findings revealed that perceived teacher discrimination was negatively related to academic achievement for both African American and Caribbean Black youth. In addition, high racial centrality and low public rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
6
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 58 publications
5
123
6
3
Order By: Relevance
“…Additionally, in one of the few studies to examine these relationships longitudinally, Wong and colleagues (2003) found that experiences with teacher and peer discrimination at school lessened achievement motivation and academic outcomes as well as the increased likelihood of problem behaviors in African American adolescents. Additional research has also demonstrated the deleterious impact on race discrimination experiences on academic-related outcomes (e.g., Burchinal, Roberts, Zeisel, & Rowley, 2008;Eccles et al, 2006;Neblett, Philip, Cogburn & Sellers, 2006;Powell & Arriola, 2003;Smalls, White, Chavous, & Sellers, 2007;Thomas, Caldwell, Faison & Jackson, 2009). Taken together, this research provides some evidence that discrimination, prejudice and other disadvantages in school settings is associated with negative educational outcomes among African American adolescents.…”
Section: Racial Climate and Achievement Outcomesmentioning
confidence: 69%
“…Additionally, in one of the few studies to examine these relationships longitudinally, Wong and colleagues (2003) found that experiences with teacher and peer discrimination at school lessened achievement motivation and academic outcomes as well as the increased likelihood of problem behaviors in African American adolescents. Additional research has also demonstrated the deleterious impact on race discrimination experiences on academic-related outcomes (e.g., Burchinal, Roberts, Zeisel, & Rowley, 2008;Eccles et al, 2006;Neblett, Philip, Cogburn & Sellers, 2006;Powell & Arriola, 2003;Smalls, White, Chavous, & Sellers, 2007;Thomas, Caldwell, Faison & Jackson, 2009). Taken together, this research provides some evidence that discrimination, prejudice and other disadvantages in school settings is associated with negative educational outcomes among African American adolescents.…”
Section: Racial Climate and Achievement Outcomesmentioning
confidence: 69%
“…college, work). For African-Americans, Thomas, Howard Caldwell, Faison, and Jackson (2009) found that public regard was not associated with academic achievement. However, they did find that public regard moderated the negative consequences of teacher discrimination.…”
Section: Discussionmentioning
confidence: 97%
“…Teachers and other students can both play equally contributory roles in perpetuating and perpetrating discrimination in the classroom, although some students report feeling more helpless in the face of teacher discrimination as compared to peer discrimination (Aroian, 2012;Thomas, Caldwell, Faison, & Jackson, 2009). Teacher discrimination can also influence the subjective sense of how well students feel that they are doing in school, regardless of their actual calculated grades.…”
Section: Teacher Discriminationmentioning
confidence: 99%
“…Teacher discrimination can also influence the subjective sense of how well students feel that they are doing in school, regardless of their actual calculated grades. Some students, in the face of discrimination from their teachers, have reported that they are doing more poorly in school (whether or not that is actually the case) than those students who do not report teacher discrimination (Thomas et al, 2009). Aroian (2012) found that Muslim youth often cope with the discrimination they face from both teachers and peers by doing nothing, both out of fear of retribution and thoughts of futility.…”
Section: Teacher Discriminationmentioning
confidence: 99%